Adaptation, mitigation and food security: Multi-criteria ranking system for climate-smart agriculture technologies illustrated for rainfed rice in Laos - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The research is published as Peer‐reviewed article in international journal